PENGARUH TEKANAN KETAATAN, KOMPLEKSITAS TUGAS DAN KEAHLIAN AUDIT TERHADAP PROFESIONALISME AUDITOR - YUSUF FAISAL; EGI GUMALA SARI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2018)
This study aims to obtain evidence on the influence of compliance pressure, task complexity, and audit expertise on the auditor's professionalism with the work environment as intervening variable at the State Audit Board of the Republic of Indonesia Riau Islands Representative. This research method is survey method with associative explanation level. The sample in this research is 38 Auditor of State Audit Board Republic of Indonesia Riau Islands Representative. The analytical techniques used are Descriptive Statistics, Classical Assumption Test, and hypothesis test, to test the hypothesis using partial test (t-test), Simultaneous Significant Test (F-test), and Intervening Variable Test. The results of this study indicate that partially known that each variable pressure of obedience, the complexity of the task of audit expertise and work environment has a direct influence on the work environment. There is a direct influence of the variable of pressure of obedience to auditor professionalism through work environment. There is a direct influence of task complexity variables on auditor professionalism through the work environment. There is a direct influence of audit skill variables on auditor professionalism through the work environment.